Know and understand centrifugal pumps - Bachus, Larry; Custodio, Angel Antonio, 1947- (Oxford ; New York : Elsevier, 2003)
Pumps are commonly encountered in industry and are essential to the smooth running of many industrial complexes. Mechanical engineers entering industry often have little practical experience of pumps and their problems, and need to build up an understanding of the design, operation and appropriate use of pumps, plus how to diagnose faults and put them right. This book tackles all these aspects in a readable manner, drawing on the authors' long experience of lecturing and writing on centrifugal pumps for industrial audiences.
Basic Pump PrinciplesChapter -- NPSH, Net Positive Suction Head -- Cavitation -- The Affinity Laws -- Useful Work and Pump Efficiency -- Pump Classification -- Understanding Pump Curves -- The System Curve -- Shaft Deflection -- Pump and Motor Alignment -- Bearings -- Pump Shaft Packing -- Mechanical Seals -- Failure Analysis of Mechanical Seals -- Failure Analysis and Correction Methods -- Avoiding Wear in Centrifugal Pumps -- Pump Piping.
Includes index.
Keywords: Centrifugal pumps; Pompes centrifuges; Electronic books